529. BV Score (Based on TRAIL, IP-10 and CRP) Accurately Distinguishes Between Bacterial and Viral Infection in Febrile Children: A Multi-Cohort Analysis. (15th December 2022) - Kaplan, Sheldon L; Arias, Cesar A; Bachur, Richard G; Ballard, Natasha; Bont, Louis J; Cruz, Andrea T; Esposito, Susanna; Gordon, Richard; Klein, Adi; Motov, Sergey M; Papan, Cihan; Rothman, Richard E; et al.
Abstract: Background: BV is a score for differentiating between bacterial and viral etiologies. Recently FDA cleared, it is based on computational integration of the blood levels of three host-proteins (TRAIL, IP-10, CRP). Here we report a multi-cohort analysis validating its diagnostic performance in comparison to a microbiology confirmed reference standard for children recruited in the Netherlands, Germany, Italy, Israel and the United States. Methods: Febrile pediatric patients (age < 18) were recruited in Emergency Departments and Urgent Care Centers in the Apollo (NCT04690569), Autopilot (NCT03052088) and Opportunity (NCT01931254) studies. Eligibility criteria included suspicion of acute bacterial or viral infection symptoms for < 7 days in patient deemed to be immunocompetent. BV is indicative of bacterial or viral infection (MeMed BV®) based on pre-defined thresholds: 0 ≤ score < 35 indicates viral (or other non-bacterial) infection, 35 ≤ score ≤ 65 indicates equivocal and 65 < score ≤ 100 indicates bacterial infection (or co-infection). BV performance was assessed against the reference standard. Three experts independently reviewed comprehensive patient data including follow-up data but were blinded to BV. A bacterial or viral microbiology confirmed reference standard required all 3 experts to assign the same etiology in addition to a positive microbiology result supporting the experts' decision (Figure legend). Results: Among the 1, 747 children recruited in the 3 studies, 861 were assigned a microbiology confirmed reference standard, with 811 viral and 50 bacterial cases (bacterial prevalence 6%). The median age was 1.8 years (interquartile range: 0.9-3.5 years), 42.3% were female, and 72.7% were diagnosed with respiratory tract infection or unspecified viral infection. BV yielded sensitivity and specificity of 95.6% (95% confidence interval: 84.9%-99.5%) and 95.4% (95%CI: 93.6%-96.8%), and negative predictive value of 99.7% (95%CI: 98.9%-99.9%), with 9.6% of cases yielding equivocal scores. Conclusion: BV accurately distinguishes bacterial from viral etiology in microbiology confirmed cases and has the potential to support clinical diagnosis in children presenting to acute care settings. Disclosures: Sheldon L. Kaplan, MD, MeMed: Advisor/Consultant|MeMed: Grant/Research Support|Pfizer: Grant/Research Support|Pfizer: Honoraria Cesar A. Arias, MD, PhD, Entasis Phramceuticals: Grant/Research Support|MeMed Diagnostics: Grant/Research Support|Merck: Grant/Research Support Richard G. Bachur, M.D., Appendicitis Biomarker: U.S. Patent|MeMed: Advisor/Consultant|MeMed: Grant/Research Support|UpToDate.com: Honoraria|Wolters-Kluwer: Honoraria Louis J Bont, M.D., MeMed: Principal Investigator (Payment made to institution for conduct of the Opportunity study) Adi Klein, M.D., MeMed: Principal Investigator (Payment made to institution for conduct of the Apollo study) Cihan Papan, M.D., MeMed: Grant/Research Support.